Cityscapes of the future : urban spaces in science fiction - Maurer, Yael, 1966-; Koren-Kuik, Meyrav (Consciousness, literature & the arts, 2018)
Cityscapes of the Future: Urban Spaces in Science Fiction offers an examination of the central role played by urban spaces in science fictional narratives in various media forms from the literary to the ludic to the cinematic. Our contributors reflect on the ways diverse urban scenarios are central to the narratives' science fictional imaginary and consider the pivotal roles cityscapes play in underscoring major thematic concerns, such as political struggles, social inequality and other cultural epistemologies. The chapters in the collection are divided into three sections examining the city and the body, cities of estrangement, and cities of the imagination.